Pengembangan Komik Matematika Materi Penyajian Data Statistika Kelas VII SMP/MTS Berbasis Budaya - Ega Dharmayani; Huri Suhendri; Yogi Wiratomo (INTELEKTIUM, 2022)
This research was conducted with the aim of designing and developing Mathematical Comics Learning Media on Cultural-Based Middle School Statistics Materials. This research was conducted on class VII junior high school students, to be precise at SMPN 36 Bekasi, SMPIT Bahana Mandiri Bekasi, and SMP Darma Patria. The development of this learning media uses a Research and Development (R&D) approach, the class-oriented ASSURE instructional design model initiated by Heinich, et al. since the 1980s and was developed by Smaldino, et al (Smaldino, 2014: 111). The ASSURE model consists of six activity steps, namely: (A) evaluate Learners (, (S)tates Standards and Objectives, (S)select Methods, Media, and Materials, (U)tilize Media and Materials, (R) require Learn Participation, (E) evaluate and Revise In this study, the product was tested on a material expert, a linguist, a development expert, a graphic design expert, 3 students who were randomly selected from 3 schools for a one to one test, 9 students randomly selected from 3 schools for the small group test, and 20 students in the large group trial to test the effectiveness of the product.